Diskursus Kebenaran Berita Berdasarkan Undang-Undang Nomor 40 Tahun 1999 Tentang Pers Dan Kode Etik Jurnalistik - Taufik Hidayat Lubis; Ismail Koto (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
The truth of news is not absolute because the truth can change, therefore the truth refers to the facts occurred. To ensure how the truth is formed, there are provisions that journalists must follow so that the news can be said to be truth. On this matter raised a problem of how a truth in the news can be formed, it can be accounted for based on Law Number 40 of 1999 concerning the Press and Journalistic Code of Ethics. Based on the research, truth in the news must refer to Law Number 40 of 1999 concerning the Press and Journalistic Code of Ethics. Truth in the news must be formed based on Article 1 number 1 of Law Number 40 of 1999 concerning the Press, "... seeking, obtaining, possessing, storing, processing, and conveying information ..." and furthermore to support journalistic activities journalists must possess what in accordance with Article 1 Press Council Regulation Number: 6/Regulation-DP/V/2008 concerning Ratification of Press Council Decree Number 03/SK-DP/III/2006 concerning Journalistic Code of Ethics As a Press Council Regulation, it was stated that "Indonesian Journalists independent, produce accurate, balanced and not in good faith news.